How Polite can Impoliteness be? A Jordanian Gendered Perspective - Bataineh, Rula Fahmi; Bataineh, Ruba F.; Andraws, Lara K. (Journal of Ethnic and Cultural Studies, 2023)
Contrary to the abundance of research on politeness in many languages, little research has been done on impoliteness, for, unlike politeness, impoliteness is essentially unmarked and, hence, defies direct observation. This study, which is informed by the work of Culpeper (1996, 2005, 2011), Brown and Levinson (1978, 1987), and Holmes (1995, 2008, 2013), attempts to examine impoliteness from a gender perspective. The data were collected from an equally divided sample of 100 male and female adults (age 20-79 years) from different regions of Jordan by means of a 31-item checklist of potentially impolite behaviors. The findings revealed an effect for gender as, despite evident similarities, male and female respondents manifest differences in their perceptions of what constitutes (im)polite behavior. The study concludes with recommendations for further research.